INNOVATIVE APPROACH IN CURRICULUM DEVELOPMENT; IMPROVING EDUCATION AND TRAINING PROGRAMS THROUGH MULTIDIMENSIONAL STRATEGIES - Akmal Mundiri; Dinda Febrianti Putri; Abdullah Abdullah (PEDAGOGIK : JURNAL PENDIDIKAN, 2024)
The rapid advancements in the digital era present educational institutions with increasingly complex challenges in maintaining curriculum relevance to the demands of the modern world. Traditional curricula, which predominantly focus on academic aspects, are increasingly viewed as insufficient in equipping graduates with the competencies required to navigate real-world challenges. Graduates are expected not only to excel academically but also to demonstrate adaptability, problem-solving capabilities, and interpersonal skills. This study investigates the potential of a multidimensional strategy to enhance curriculum design by integrating key elements, such as digital competencies, quality of learning materials, effective technology utilization, and active stakeholder involvement. Utilizing qualitative methods, the research collected data through interviews with students, educators, educational managers, and technology developers to gather insights on best practices and the inherent challenges in curriculum innovation. The research findings indicate that the implementation of multidimensional strategies in curriculum development includes the integration of social and emotional skills, enhancement of learning material quality, utilization of technology in learning, cross-sectoral collaboration, and the development of practical skills.